OVERVIEW OF THE DEVELOPMENT OF UNDERGRADUATE SOFTWARE ENGINEERING EDUCATION IN GREAT BRITAIN (Comparative Professional Pedagogy, 2024)
The article analyzes the retrospective development of undergraduate education in software engineering in Great Britain. The Quality Assurance Agency for Higher Education (QAA) activities are characterized. The main regulatory documents governing the activities of UK universities in IT education and software engineering education are analyzed.It is established that computing is a relatively new field of knowledge; therefore, the first higher education standard in this area was created by QAA in 2000. This standard provided general recommendations for the development of new programs while maintaining flexibility and the possibility of introducing innovations in the educational process.It is found that in the period from 2000 to 2007, the main changes included the introduction of the concept of “computational thinking,” which refers to basic analytical skills important for everyday life, and the definition of certain skills and abilities were revised as well.It is emphasized that with the rapid development of information technologies, QAA adequately responds to challenges and continues to update the higher education standard in the field of computing. It is established that in the period from 2007 to 2016, significant changes occurred in the standards of education. In 2015, QAA updated the standard, taking into account the recommendations of the Association for Computing Machinery and the IEEE Computer Society. This standard included new requirements for software development, design, testing, and maintenance, and emphasized the importance of developing problem-solving skills, teamwork, communication, and ethical responsibility.Considering current trends in the development of software engineering education in the UK, it is noted that the period from 2016 to 2022 is characterized by further updates to the standard aimed at increasing the flexibility of educational programs. An important innovation was the expansion of cybersecurity skills and an emphasis on the development of critical thinking, initiative, and creativity. The updated standard also takes into account the impact of the COVID-19 pandemic, which led to a massive shift to distance learning. Additionally, principles of sustainable development are applied in software engineering.Overall, the evolution of software engineering education in the UK has been highlighted, emphasizing the adaptability and innovativeness of educational programs that meet current requirements of the labor market and contribute to the development of competitive specialists.
Keywords: Bachelor of Software Engineering; the field of computing; Quality Assurance Agency for Higher Education; professional training; universities; Great Britain; regulatory documents